Thermal characteristics of kerosene oil-based hybrid nanofluids (Ag-MnZnFe2O4): A comprehensive study - Ahmad, Sohail; Ali, Kashif; Haider, Tahir; Jamshed, Wasim; Tag El Din, El Sayed M.; Hussain, Syed M. (Frontiers in Energy Research, 2022)
Hybrid nanofluids are new and most fascinating types of fluids that involve superior thermal characteristics. These fluids exhibit better heat transfer performance as equated to conventional fluids. Our concern, in this paper, is to numerically interpret the Kerosene oil based hybrid nanofluids comprising of dissimilar nanoparticles like Silver (Ag) and Manganese zinc ferrite (MnZnFe2O4). A numerical algorithm, which is mainly based on finite difference discretization, is developed to find the numerical solution of the problem. A numerical comparison appraises the efficiency of this algorithm. The effects of physical parameters are examined via the graphical representations in either case of nanofluids (pure or hybrid). The results designate that the porosity of the medium causes a resistance in the fluid flow. The enlarging values of nanoparticles volume fraction of Silver sufficiently increase the temperature as well as velocity. It is examined here that mixture of hybrid nanoparticles (Ag-MnZnFe2O4) together with Kerosene oil (KO) can provide assistance in heating up the thermal systems.